Pediatric tracheotomy: 5-years of experiences at a tertiary care center - Duymaz, Yaşar Kemal; Şahin Yılmaz, Aslı; Önder, Serap; Tarlanova, Arzu; Gergin Tinay, Özgül (Istanbul University, 2021)
Objective: To describe specific indications and complications of pediatric tracheostomies performed in our tertiary care children’s hospital between 2015 and 2020. Materials and Methods: A retrospective study analyzing charts of pediatric tracheostomies utilizing the maturation suture technique was conducted. The review included patient data covering a 5-year period, commencing on the 1st of January 2015 through the 31st of May 2020. Results: Fifty-five patients (33 females, 22 male) were included in the study. A tracheostomy was performed to address complications arising from prolonged ventilation in 48 children (87%) or upper airway obstruction in 7 children (13%). There was one intraoperative complication that resulted in death. There was one early postoperative complication (2%) (one child suffered accidental decannulation and the cannula was replaced without further incident). There were 7 late postoperative complications all featuring peristomal granulation tissue (13%). There were 16 deaths; however, only one resulted from the tracheostomy as outlined above. Eight patients (15%) were successfully decannulated. In 6 cases, the tracheostomy was spontaneously closed. Repair of tracheoesophageal fistula was required in two patients. Conclusion: Currently, the tracheostomy is the preferred course of treatment. Though it can potentially lead to severe complications in children, instances of this occurring are rare. Therefore, a tracheostomy should be performed by a multidisciplinary team following predetermined rules in a specialized center.
Keywords: Pediatric Tracheotomy; Maturation Suture Technique; Upper Airway Obstruction